2014
DOI: 10.1002/anie.201401075
|View full text |Cite
|
Sign up to set email alerts
|

The Biocatalytic Repertoire of Natural Biaryl Formation

Abstract: The catalytic and selective construction of carbon-carbon bonds for the generation of complex molecules is one of the most important tasks in organic chemistry. This was clearly highlighted by the 2010 Nobel Prize in Chemistry, which was awarded for the development of Pd-catalyzed cross-coupling reactions. The underlying concept of cross-linking building blocks to generate molecular complexity can also be widely found in natural product biosynthesis. Impressive examples for such natural cross-coupling reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 97 publications
1
98
0
1
Order By: Relevance
“…19,20 Consistent with the underlying biochemical logic for the oxidative coupling of aryl rings, 21 our studies revealed that naturally produced OH-BDEs and di-OH-BDEs are assembled via the biradical homo- and heterocoupling of bromophenol and bromocatechol monomers mediated by cytochrome P450 enzymes. Recently, additional biotic 22 and abiotic 23 radical coupling processes have been reported for OH-BDE syntheses.…”
Section: Introductionsupporting
confidence: 76%
“…19,20 Consistent with the underlying biochemical logic for the oxidative coupling of aryl rings, 21 our studies revealed that naturally produced OH-BDEs and di-OH-BDEs are assembled via the biradical homo- and heterocoupling of bromophenol and bromocatechol monomers mediated by cytochrome P450 enzymes. Recently, additional biotic 22 and abiotic 23 radical coupling processes have been reported for OH-BDE syntheses.…”
Section: Introductionsupporting
confidence: 76%
“…The pioneering work of Zenk as well as subsequent studies showed that intramolecular phenol coupling during alkaloid biosynthesis is catalyzed regioselectively and stereoselectively by cytochrome P450 enzymes (Gerardy and Zenk, 1992;Gesell et al, 2009). Furthermore, there is a growing number of examples also for bimolecular couplings that are mediated by cytochrome P450s, laccases, or peroxidases in a stereospecific manner (Schlauer et al, 1998;Niemetz and Gross, 2003;Fang et al, 2012;Aldemir et al, 2014;Mazzaferro et al, 2015). Stereochemical control by the oxidizing enzymes alleviates the need for any DIR activity.…”
mentioning
confidence: 99%
“…The involvement of the flavoenzyme suggests an electrophilic aromatic substitution as the biosynthetic mechanism for the homocoupling. Such a biosynthesis is in clear contrast to the phenol oxidative coupling usually observed for C , C ‐coupled biaryls 5. Rotation around the heterobiaryl axis in 1 and 2 is hampered at ambient temperatures, leading to separable enantiomers, of which only the ( M ) isomer has been found in the bacterial producer.…”
Section: Introductionmentioning
confidence: 89%